DEVELOPING “ERT (ENGLISH RECOUNT TEXT)” APPLICATION FOR TEACHING WRITING TO TENTH GRADE SENIOR HIGH SCHOOL STUDENTS - Nurjanah, Suci; Puspita Sari, Hesty (JOSAR (Journal of Students Academic Research), 2024)
Abstract This study aimed to establish the potency of the ERT application as a learning tool in writing class X learners in high school. The researchers created a writing lesson application by employing research and development (R&D) design. According to the findings of class X student interviews at SMAN 1 Sutojayan and SMAN 1 Kademangan, the researcher discovered that students had writing difficulties. The study's participants were twenty randomly chosen students from the two schools and five randomly chosen teachers in Blitar Regency. The ERT Application's findings indicate that: (1) this application comprises of writing exercises and recount text material, and it comes with two guidebooks for teachers and students; (2) the validity of this application as a learning tool, with 89% of the information and 84% of the media being validated; (3) both teachers and students had favorable opinions of the ERT application as a teaching tool. While the ERT model received an overall student response of 86% and an overall teacher response of 86% in the product test findings, both groups highly agreed with ERT application. The product significantly influences how well students can produce recount It is reliable and suitable for use as a teaching and learning tool. Keywords: Developing, ERT-Application, Writing, Recount Text